Time evolution after double trace deformation - Masamichi Miyaji (Journal of High Energy Physics, 2018)
Abstract In this paper, we consider double trace deformation to single CFT2, and study time evolution after the deformation. The double trace deformation we consider is nonlocal: composed of two local operators placed at separate points. We study two types of local operators: one is usual local operator in CFT, and the other is HKLL bulk local operator, which is still operator in CFT but has properties as bulk local operator. We compute null energy and averaged null energy in the bulk in both types of deformations. We confirmed that, with the suitable choice of couplings, averaged null energies are negative. This implies causal structure is modified in the bulk, from classical background. We then calculate time evolution of entanglement entropy and entanglement Rényi entropy after double trace deformation. We find both quantities are found to show peculiar shockwave-like time evolution.